Fiat cura, et pereat mundus: la fenomenología del cuidado y del compromiso en Husserl - de Warren, Nicolas (2022)
The present paper explores “the importance of what we care about” from a phenomenological angle in the spirit of Frankfurt’s seminal essay. I shallreflect upon a few of its central concepts and issues within a Husserlian frame of analysis. My overarching claim is that Frankfurt’s threefold distinction – knowing,ethical conduct, caring – is equally central to Husserl’s phenomenology of reason and, more directly, underlies Husserl’s phenomenological ethics of values andvocation in his Freiburg manuscripts of the 1920s and 1930s.